Recent advances in hydrophilic interaction chromatography for quantitative analysis of endogenous and pharmaceutical compounds in plasma samples. (September 2014) - Isokawa, Muneki; Kanamori, Takahiro; Funatsu, Takashi; Tsunoda, Makoto
There is an increasing need for new analytical methods that can handle a large number of analytes in complex matrices. Hydrophilic interaction chromatography (HILIC) has recently been demonstrated as an important supplement to reversed-phase liquid chromatography for polar analytes, particularly endogenous compounds. With the increasing popularity of HILIC, progressively more polar phases with diverse functional groups have been developed. In addition, the coupling of HILIC to mass spectrometry offers the advantages of improved sensitivity by employing an organic-rich mobile phase. This article reviews recent applications of HILIC for the analysis of endogenous and pharmaceutical compounds in plasma samples. Furthermore, based on recent studies, we provide a discussion of column selection, sample pretreatment for HILIC analysis, and detection sensitivity.